Analisis Proses Kearsipan Digital Berbasis Document Management System pada Sekretaris Perusahaan PT Asuransi Jasa Indonesia - Firda Fadila; Darma Rika Swaramarinda; Eka Dewi Utari (Jurnal Publikasi Ilmu Manajemen, 2025)
This study aims to explore and analyze how the web-based digital archiving process of Document Management System (DMS) works for both incoming and outgoing mail, as well as the obstacles faced in the archiving of company secretaries at PT Asuransi Jasa Indonesia. This study uses a descriptive qualitative research method with a case study. Data sources were collected through observation, interviews, and documentation with employees of the Corporate Secretary of PT Asuransi Jasa Indonesia as informants. Data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the process of filing incoming and outgoing letters and digitally inputting archives in the filing system at PT Asuransi Jasa Indonesia is operational, but there are still several obstacles with the website, ranging from login problems, unstable upload processes, and scanned archives that have not been fully entered into the system. This method allows the agency to save physical storage space while providing more efficient access to employees and users. Thus, the research efforts can be concluded that the digital archiving process can be beneficial to the company, such as operational efficiency.